The neuromuscular determinants of unilateral jump performance in soccer players are direction-specific - Murtagh, C. F.; Nulty, C.; Vanrenterghem, J.; O`Boyle, A.; Morgans, R.; Drust, B.; Erskine, R. M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate differences in neuromuscular factors between elite and nonelite players and to establish which factors underpin direction-specific unilateral jump performance. Methods: Elite (n=23; age, 18.1 [1.0] y; body mass index, 23.1 [1.8] kg·m-2) and nonelite (n=20; age, 22.3 [2.7] y; body mass index, 23.8 [1.8] kg·m-2) soccer players performed 3 unilateral countermovement jumps (CMJs) on a force platform in the vertical, horizontal-forward, and medial directions. Knee extension isometric maximum voluntary contraction torque was assessed using isokinetic dynamometry. Vastus lateralis fascicle length, angle of pennation, quadriceps femoris muscle volume (Mvol), and physiological cross-sectional area (PCSA) were assessed using ultrasonography. Vastus lateralis activation was assessed using electromyography. Results: Elite soccer players presented greater knee extensor isometric maximum voluntary contraction torque (365.7 [66.6] vs 320.1 [62.6] N·m; P=.045), Mvol (2853 [508] vs 2429 [232] cm3; P=.001), and PCSA (227 [42] vs 193 [25] cm2; P=.003) than nonelite. In both cohorts, unilateral vertical and unilateral medial CMJ performance correlated with Mvol and PCSA (r=.310, P=.043). In elite soccer players, unilateral vertical and unilateral medial CMJ performance correlated with upward phase vastus lateralis activation and angle of pennation (r=.478, P=.028). Unilateral horizontal-forward CMJ peak vertical power did not correlate with any measure of muscle size or activation but correlated inversely with angle of pennation (r=-.413, P=.037). Conclusions: While larger and stronger quadriceps differentiated elite from nonelite players, relationships between neuromuscular factors and unilateral jump performance were shown to be direction-specific. These findings support a notion that improving direction-specific muscular power in soccer requires improving a distinct neuromuscular profile.